Improving Firebase BaaS Service Security in Counseling Chat Applications: AES-256 and CBC Approach for End-to-End Encryption - Nurhandhi, Mogar; Suhendar, Agus (JISA(Jurnal Informatika dan Sains), 2023)
The activities of using the internet and exchanging information and sending messages have used a lot of internet media, one of which is chat message media, but over time data and information security problems in chat messages that are often encountered are active and passive wiretapping. In this research, the author wants to create a counseling chat message security application using the AES (Advanced Encryption Standard) algorithm cryptographic method combined with the CBC (Cipher Block Chaining) technique which is an advanced development of the ECB (Electronic Code Book) technique. AES basically uses a block cipher with a length of 128 bits as the default operation, and the key length size varies from 128, 192 and 256 bits. so AES uses a 4x4 matrix equation with each section having a size of 1 byte. From these problems, research will be conducted to develop an application to accommodate the counseling process using a chat application that has the main focus of securing messages with image types and stored in the Firebase database service (Backend as a Service). As well as using the End-to-End service principle so that users do not need to do the encryption or decryption process directly because the process has been carried out by the system, this will also provide more security aspects in terms of confidentiality of key data and initialization vectors. So that the process of exchanging information using the media chat counseling application is secured and avoids tapping by irresponsible parties.